Pharmacological evidence of calcium-activated and voltage-gated potassium channels in human platelets. - de Silva, H; Carver, J; Aronson, J (1997)
1. Previous electrophysiological studies have suggested the presence of KCa and Kv channels in human platelets. However, the pharmacology of these channels has not been defined. 2. We have studied potassium channels in human platelets by measuring the efflux of 86Rb+ (a marker for K+) from 86Rb(+)-loaded cells, and have defined their responses to stimulation by the platelet agonist thrombin and the calcium ionophore ionomycin. 3. Thrombin (0.1-0.6 i.u./ml) stimulated an increase in 86Rb+ efflux from the platelets in a concentration-dependent manner. This efflux was significantly inhibited by apamin (100 nmol/l), charybdotoxin (300 nmol/l) and alpha-dendrotoxin (100-200 nmol/l), blockers of SKCa channels, KCh channels and Kv channels respectively. Iberiotoxin (300 nmol/l), a specific inhibitor of BKCa channels, had no effect on the thrombin-stimulated 86Rb+ efflux. Although glibenclamide, an inhibitor of KATP channels, inhibited the thrombin-stimulated efflux, it did so only in a high concentration (20 mumol/l). 4. Ionomycin (1-5 mumol/l) stimulated an increase in 86Rb+ efflux from the platelets in a concentration-dependent manner. This efflux was significantly inhibited by apamin (100 nmol/l) and charybdotoxin (300 nmol/l). However, iberiotoxin (300 nmol/l) had no effect on the ionomycin-stimulated 86Rb+ efflux. 5. These findings suggest that 86Rb+ efflux from platelets stimulated by thrombin and ionomycin occurs via two types of KCa channel: SKCa and KCh channels. Thrombin also stimulated efflux via Kv channels.